Active carbon fiber catalytic net for purifying air as well as preparation method and application of active carbon fiber catalytic net

By using a plasma generator in the air purification device to uniformly attach the activated carbon fibers to the metal frame, and combining hot melt adhesive and titanium dioxide photocatalyst, the problem of uneven distribution of activated carbon is solved, the air purification efficiency and service life are improved, and the air purification efficiency and service life are reduced. Air flow resistance and energy consumption.

CN119175092APending Publication Date: 2024-12-24JINAN CHENGDU BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411387892.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In the air purification device, the existing activated carbon catalytic networks have uneven distribution of activated carbon, resulting in uneven adsorption capacity, shortened service life, increased pressure loss and reduced mechanical strength.

Method used

The plasma generator is used to uniformly attach the activated carbon fibers to the metal frame under the action of an electric field, and a uniformly distributed activated carbon fiber catalytic web is formed by combining hot melt adhesive and spraying the titanium dioxide photocatalyst.

Benefits of technology

The uniformity of activated carbon distribution is achieved, the air purification efficiency and service life is improved, and the air flow resistance and energy consumption are reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of air purification, in particular to an air purification activated carbon fiber catalysis net and a preparation method and application thereof. The metal frame serves as a supporting framework of the activated carbon fiber catalytic net, the surface of the metal frame is coated with the hot melt adhesive and then connected with a negative electric field of a plasma generator, and activated carbon fibers are connected with a positive electric field of plasma; the activated carbon fibers are uniformly distributed on the metal frame with the surface coated with the hot melt adhesive under the action of an electric field, and then the activated carbon fibers are uniformly distributed on the metal frame which is coated with the hot melt adhesive and connected with a negative electric field of a plasma generator; and then spraying a photocatalyst on the surface of the activated carbon fiber to prepare the air-purifying activated carbon fiber catalytic net.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air purification, and in particular to an air-purifying activated carbon fiber catalytic net and a preparation method and application thereof. Background Art

[0002] In air purification devices, there is a filtering part used to capture and remove pollutants in the air. Activated carbon has excellent adsorption properties and can effectively adsorb harmful gases, odor molecules or pollutants in industrial emissions (such as formaldehyde, benzene, ammonia and other volatile organic compounds or other air pollutants) in the air. The metal frame can serve as a supporting structure, providing sufficient mechanical strength to form a filter net to withstand the pressure during the filtration process, and can also maintain the integrity of the activated carbon layer. Therefore, activated carbon is often coated on a metal frame to form an activated carbon catalytic net as the filtering part of the air purification device.

[0003] Activated carbon catalytic mesh is usually prepared by pressing activated carbon into a honeycomb structure or bonding activated carbon powder to a honeycomb aluminum mesh and drying it. Although this preparation method can provide a certain degree of mechanical strength and structural stability, it may lead to problems such as a relatively small surface area of ​​activated carbon and uneven distribution of activated carbon. Uneven coating of activated carbon will cause the adsorption capacity of some areas to be insufficient to achieve the expected purification effect, reducing the overall air purification efficiency; and the unevenness of the activated carbon layer may cause some areas to be saturated prematurely, while other areas still have residual adsorption capacity, so uneven use will shorten the service life of the entire filter material. Not only that, uneven coating of activated carbon may also cause uneven resistance when air flows through the filter material, increase the pressure loss of the system, and increase energy consumption; in addition, uneven coating may produce stress concentration points on the surface of the metal frame, affecting the long-term stability and mechanical strength of the material. Summary of the invention

[0004] The purpose of the present invention is to provide an activated carbon fiber catalytic net for purifying air and a preparation method and application thereof, so that the activated carbon is evenly distributed.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] A method for preparing an activated carbon fiber catalytic net for purifying air comprises the following steps:

[0007] Applying hot melt adhesive on the metal frame to form a metal frame coated with hot melt adhesive;

[0008] The metal frame coated with hot melt adhesive is connected to the negative electric field end of the plasma generator; the activated carbon fiber is placed at the positive electric field end of the plasma generator; after power is turned on, the activated carbon fiber is attached to the metal frame coated with hot melt adhesive under the action of the electric field; and then heated to obtain an activated carbon fiber net;

[0009] The photocatalyst is sprayed on the activated carbon fiber net to form a photocatalyst layer, thereby obtaining the air-purifying activated carbon fiber catalytic net.

[0010] Optionally, the metal frame comprises a honeycomb aluminum mesh or a nickel mesh.

[0011] Optionally, the ratio of the amount of activated carbon fiber to the surface area of ​​the metal frame is 3-10 g: 2 cm 2 .

[0012] Optionally, the voltage of the plasma generator is 8 to 10 kV, the discharge power is 8 to 20 W, and the power-on time is 5 to 20 min.

[0013] Optionally, the heating temperature is 80-130° C. and the heating time is 40-75 seconds.

[0014] Optionally, the photocatalyst comprises titanium dioxide, and the thickness of the photocatalyst layer is 0.5 to 1 μm.

[0015] The invention provides an air-purifying activated carbon fiber catalytic net obtained by the preparation method.

[0016] The invention also provides application of the air-purifying activated carbon fiber catalytic net in an air purification system.

[0017] In the preparation process of the air-purifying activated carbon fiber catalytic net of the present invention, the metal frame plays a role of skeleton support, which is conducive to the molding of the activated carbon fiber catalytic net, so that the activated carbon fiber can maintain a certain shape and size, and is easy to install and maintain. In the preparation process, the activated carbon fiber is connected to the positive electric field of the plasma generator. Under the action of the electric field, the activated carbon fiber moves according to the principle of positive and negative electron attraction under the influence of positive ions, and is evenly distributed on the metal frame coated with hot melt adhesive connected to the negative electric field of the plasma generator, and basic adhesion is achieved by hot melt adhesive. In the subsequent heating process, the activated carbon fiber is combined with the metal frame by hot melt adhesive.

[0018] In the preparation process of the present invention, the activated carbon fiber has a microporous structure and a higher surface area, and has excellent gas adsorption performance. Titanium dioxide is a photocatalytic material that can operate at room temperature. It is sprayed on the surface of the evenly distributed activated carbon fiber, so that the prepared air-purifying activated carbon fiber catalytic net can adsorb harmful gases and catalyze gas decomposition.

[0019] The preparation method of the air-purifying activated carbon fiber catalytic net provided by the present invention can simply and quickly prepare the air-purifying activated carbon fiber catalytic net with uniform distribution of activated carbon, thereby improving its application effect and service life. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing an activated carbon fiber catalytic net for purifying air, comprising the following steps:

[0021] Applying hot melt adhesive on the metal frame to form a metal frame coated with hot melt adhesive;

[0022] The metal frame coated with hot melt adhesive is connected to the negative electric field end of the plasma generator; the activated carbon fiber is placed at the positive electric field end of the plasma generator; after power is turned on, the activated carbon fiber is attached to the metal frame coated with hot melt adhesive under the action of the electric field; and then heated to obtain an activated carbon fiber net;

[0023] The photocatalyst is sprayed on the activated carbon fiber net to form a photocatalyst layer, thereby obtaining the air-purifying activated carbon fiber catalytic net.

[0024] In the present invention, the metal frame preferably comprises a honeycomb aluminum mesh or a nickel mesh; the metal frame is preferably 4 to 10 meshes, more preferably 5 to 8 meshes, and even more preferably 6 to 7 meshes.

[0025] In the present invention, the metal frame is preferably cleaned before being adhered with the hot melt adhesive, and the cleaning is preferably carried out by ultrasonic cleaning, water washing and drying in sequence;

[0026] The solution for the ultrasonic cleaning is not particularly limited and can be determined according to actual conditions. The conditions for the ultrasonic cleaning are not particularly limited and can be any solution that can complete the cleaning.

[0027] The conditions for the water washing are not particularly limited, and any conditions that can complete the washing are acceptable;

[0028] The drying conditions are not particularly limited, and any conditions that can achieve drying are acceptable.

[0029] In the present invention, the hot melt adhesive is not particularly limited, and any adhesive that can achieve adhesion is acceptable.

[0030] In the present invention, the ratio of the amount of activated carbon fiber to the surface area of ​​the metal frame is 3-10 g: 2 cm 2 .

[0031] In the present invention, the activated carbon fiber is preferably purchased or homemade, and the method for preparing the activated carbon fiber is preferably: washing, carbonizing and activating the organic fiber raw material in sequence to obtain the activated carbon fiber;

[0032] The organic fiber raw material preferably comprises at least one of phenolic resin, cellulose base, polyvinyl alcohol, asphalt or polyphenylene nitrile;

[0033] The cleaning is preferably performed by immersing the organic fiber raw material in a salt solution and then drying. The salt solution is preferably at least one of a phosphate solution, a carbonate solution, a sulfate solution or an ammonium chloride solution. The drying conditions are not particularly limited and any conditions that can achieve drying are sufficient. The cleaning treatment can prevent certain fibers from melting during high-temperature carbonization and activation.

[0034] The carbonization temperature is preferably 350-500°C, more preferably 400-450°C, the time is preferably 45-90 min, more preferably 60-80 min, and the heating rate is preferably 5-15°C / min, more preferably 10-12°C / min; the carbonization is preferably carried out in a nitrogen atmosphere, which can remove volatile non-carbon components in the fiber;

[0035] The activation temperature is preferably 600-1000°C, more preferably 700-900°C, and more preferably 750-800°C; the activation time is preferably 45-80min, more preferably 50-75min, and more preferably 55-60min; the activation agent is preferably at least one of water vapor, air, or carbon dioxide; the activation agent flow rate is preferably 50-120L / min. More preferably, it is 60-100L / min, and more preferably 75-90L / min; activation can generate abundant micropores and increase the specific surface area of ​​activated carbon fiber.

[0036] In the present invention, the voltage of the plasma generator is preferably 8-10 kV, more preferably 8.5-9 kV; the discharge power is preferably 8-20 W, more preferably 9-18 W, and more preferably 10-15 W; the power-on time is preferably 40-75 s, more preferably 45-70 s, and more preferably 50-60 s.

[0037] In the present invention, the heating temperature is preferably 80 to 130° C., more preferably 90 to 120° C., and even more preferably 100 to 110° C.; the heating time is preferably 5 to 20 min, and even more preferably 10 to 15 min.

[0038] In the present invention, the photocatalyst preferably comprises titanium dioxide, and the thickness of the photocatalyst layer is preferably 0.5 to 1 μm, more preferably 0.5 to 0.9 μm, and even more preferably 0.6 to 0.8 μm.

[0039] The invention provides an air-purifying activated carbon fiber catalytic net obtained by the preparation method.

[0040] The invention also provides application of the air-purifying activated carbon fiber catalytic net in an air purification system.

[0041] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0042] Example 1

[0043] The discarded cotton cloth is washed with water, then soaked in an ammonium chloride solution with a mass concentration of 15% for 10 hours and then naturally dried; after drying, the cotton cloth is placed in a tubular furnace, heated to 500°C at a heating rate of 12°C / min in a nitrogen atmosphere, and carbonized for 45 minutes, then carbon dioxide is introduced at a rate of 90L / min, the temperature is raised to 800°C in a carbon dioxide atmosphere, and activated for 60 minutes to obtain the activated carbon fiber.

[0044] A 6-mesh honeycomb aluminum mesh is ultrasonically cleaned and then dried at room temperature, and coated with hot melt adhesive to form a honeycomb aluminum mesh coated with hot melt adhesive, and a negative electric field end of a plasma generator is connected to the honeycomb aluminum mesh;

[0045] The activated carbon fiber prepared by the above method is placed at the positive electric field end of the plasma generator. After power is turned on, activated carbon fibers carrying positive ions are formed. The ratio of the amount of activated carbon fiber to the surface area of ​​the metal frame is 6g:2cm 2 ; The voltage of the plasma generator is 8kV, the discharge power is 15W, and the power-on time is 60s;

[0046] Under the action of the electric field of the plasma generator, the activated carbon fibers carrying positive ions are evenly distributed on the metal frame coated with hot melt adhesive; then heated at 90°C for 10 minutes to obtain an activated carbon fiber web;

[0047] Titanium dioxide is sprayed on the activated carbon fiber net to form a titanium dioxide layer with a thickness of 0.5 μm; and the air-purifying activated carbon fiber catalytic net is obtained.

[0048] Example 2

[0049] A 5-mesh nickel mesh is ultrasonically cleaned and then dried at room temperature, and coated with hot melt adhesive to form a nickel mesh coated with hot melt adhesive, and a negative electric field end of a plasma generator is connected to the nickel mesh;

[0050] The activated carbon fiber prepared by the method described in Example 1 was placed at the positive electric field end of the plasma generator. After power was turned on, activated carbon fibers carrying positive ions were formed. The ratio of the amount of activated carbon fiber to the surface area of ​​the metal frame was 7 g: 2 cm 2 ; The voltage of the plasma generator is 9kV, the discharge power is 18W, and the power-on time is 60s;

[0051] Under the action of the electric field of the plasma generator, the activated carbon fibers carrying positive ions are evenly distributed on the metal frame coated with hot melt adhesive; then heated at 100°C for 10 minutes to obtain an activated carbon fiber web;

[0052] Titanium dioxide is sprayed on the activated carbon fiber net to form a titanium dioxide layer with a thickness of 0.5 μm; and the air-purifying activated carbon fiber catalytic net is obtained.

[0053] Test Case

[0054] The air purification activated carbon fiber catalytic nets prepared in Example 1 and Example 2 were subjected to a partitioned adsorption test;

[0055] Each air-purifying activated carbon fiber catalytic net is randomly selected from five unconnected partitions using a guide cover, which are respectively recorded as areas 1 to 5. The same concentration of formaldehyde is introduced into each partition to perform a formaldehyde removal test on the air-purifying activated carbon fiber catalytic net. The residual formaldehyde content of each partition is detected at 1h, 3h, 6h, 12h and 24h after the start of the test, and the removal rate is calculated. The test results of the air-purifying activated carbon fiber catalytic net obtained in Example 1 are shown in Table 1, and the test results of the air-purifying activated carbon fiber catalytic net obtained in Example 2 are shown in Table 2:

[0056] Table 1 Test of the adsorption performance of the activated carbon fiber catalytic net for air purification prepared in Example 1

[0057] 1h 3h 6h 12h 24h Region 1 53.7% 72.4% 86.7% 91.4% 97.8% Area 2 53.6% 72.4% 86.4% 91.6% 98.0% Area 3 53.6% 72.6% 86.6% 91.3% 97.7% Region 4 53.8% 72.3% 86.4% 91.4% 97.8% Area 5 53.7% 72.4% 86.4% 91.5% 97.9%

[0058] Table 2 Test of the adsorption performance of the activated carbon fiber catalytic net for air purification prepared in Example 2

[0059] 1h 3h 6h 12h 24h Region 1 52.2% 74.7% 87.3% 92.2% 98.5% Area 2 52.4% 74.7% 87.4% 92.3% 98.6% Area 3 52.3% 74.6% 87.6% 92.2% 98.3% Region 4 52.4% 74.8% 87.4% 92.3% 98.4% Area 5 52.3% 74.8% 87.5% 92.3% 98.4%

[0060] It can be found from Tables 1 to 2 that the air-purifying activated carbon fiber catalytic nets prepared in Examples 1 and 2 have continuous formaldehyde adsorption and degradation performance, and the adsorption capacity of each area of ​​the air-purifying activated carbon fiber catalytic net is always the same, which can indicate that the activated carbon on the air-purifying activated carbon fiber catalytic net is evenly distributed. Activated carbon adsorption is a relatively fast process, while photocatalytic decomposition requires a certain reaction time. Therefore, the formaldehyde adsorption test is mainly for the adsorption and purification of activated carbon in the early stage, and the photocatalytic reaction is gradually added in the later stage to decompose the formaldehyde deposited on the activated carbon fiber, so that the activated carbon fiber has continuous adsorption capacity.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an activated carbon fiber catalytic net for purifying air, characterized in that: The following steps are involved: Applying hot melt adhesive on the metal frame to form a metal frame coated with hot melt adhesive; Connect the metal frame coated with hot melt adhesive to the negative electric field end of the plasma generator; place the activated carbon fiber at the positive electric field end of the plasma generator; after power is turned on, under the action of the electric field, the activated carbon fiber adheres to the metal frame coated with hot melt adhesive; Subsequently, heating is performed to obtain an activated carbon fiber web; The photocatalyst is sprayed on the activated carbon fiber net to form a photocatalyst layer, thereby obtaining the air-purifying activated carbon fiber catalytic net.

2. The preparation method according to claim 1, characterized in that: The metal frame comprises a honeycomb aluminum mesh or a nickel mesh.

3. The preparation method according to claim 1, characterized in that: The ratio of the amount of activated carbon fiber to the surface area of ​​the metal frame is 3-10 g: 2 cm 2 .

4. The preparation method according to claim 1, characterized in that: The voltage of the plasma generator is 8-10 kV, the discharge power is 8-20 W, and the power-on time is 40-75 s.

5. The preparation method according to claim 1, characterized in that: The heating temperature is 80-130° C. and the heating time is 5-20 minutes.

6. The preparation method according to claim 1, characterized in that: The photocatalyst includes titanium dioxide, and the thickness of the photocatalyst layer is 0.5 to 1 μm.

7. An activated carbon fiber catalytic net for purifying air obtained by the preparation method according to any one of claims 1 to 6.

8. Use of the air-purifying activated carbon fiber catalytic net according to claim 7 in an air purification system.